Fluorescent Aptamer Paper-Based Chip Sensor for Highly Sensitive Detection of Cd2+ in Lettuce - SHEN Haoshuang, LI Chen, LI Xinpei, QIAN Shiquan, YAN Xu, YUAN Min, XU Fei (Shipin Kexue)
A fluorescent aptamer paper-based chip sensor was developed for the rapid and highly sensitive on-site detection of Cd2+. In this sensor, based on the strong specific binding between fluorescence-labeled aptamer and Cd2+, a competitive fluorescence turn-on strategy was adopted. The quencher-labeled complementary chain was flushed to the waste liquid area, and the strong fluorescence signal reappeared in the detection area and was captured by a smartphone. Changes in fluorescence signal were analyzed by ImageJ software for RGB. The fluorescence signal of the sensor increased linearly with Cd2+ concentration in the range of 10 to 500 nmol/L, and the detection limit was 0.83 nmol/L. The sensor demonstrated excellent tolerance to interference from other co-existing ions in complex environments while maintaining high specificity for detecting Cd2+. Furthermore, the sensor was successfully applied to the quantitative detection of Cd2+ in lettuce samples with a sensitivity higher than 22.48 μg/kg, recoveries of 96.34%–98.31% and relative standard deviation (RSD) less than 12%. Therefore, this sensor is suitable for the rapid detection of trace hazards such as heavy metals in fruits, vegetables and agricultural products.